Successes and challenges of health systems governance towards universal health coverage and global health security: a narrative review and synthesis of the literature - Ayal Debie; Resham B. Khatri; Yibeltal Assefa (BMC, 2022)
Abstract Background The shift in the global burden of disease from communicable to noncommunicable was a factor in mobilizing support for a broader post-Millennium Development Goals (MDGs) health agenda. To curb these and other global health problems, 193 Member States of the United Nations (UN) became signatories of the Sustainable Development Goals (SDGs) and committed to achieving universal health coverage (UHC) by 2030. In the context of the coronavirus disease 2019 (COVID-19) pandemic, the importance of health systems governance (HSG) is felt now more than ever for addressing the pandemic and continuing to provide essential health services. However, little is known about the successes and challenges of HSG with respect to UHC and health security. This study, therefore, aims to synthesize the evidence and identify successes and challenges of HSG towards UHC and health security. Methods We conducted a structured narrative review of studies published through 28 July 2021. We searched the existing literature using three databases: PubMed, Scopus and Web of Science. Search terms included three themes: HSG, UHC and health security. We synthesized the findings using the five core functions of HSG: policy formulation and strategic plans; intelligence; regulation; collaboration and coalition; and accountability. Results A total of 58 articles were included in the final review. We identified that context-specific health policy and health financing modalities helped to speed up the progress towards UHC and health security. Robust health intelligence, intersectoral collaboration and coalition were also essential to combat the pandemic and ensure the delivery of essential health services. On the contrary, execution of a one-size-fits-all HSG approach, lack of healthcare funding, corruption, inadequate health workforce, and weak regulatory and health government policies were major challenges to achieving UHC and health security. Conclusions Countries, individually and collectively, need strong HSG to speed up the progress towards UHC and health security. Decentralization of health services to grass root levels, support of stakeholders, fair contribution and distribution of resources are essential to support the implementation of programmes towards UHC and health security. It is also vital to ensure independent regulatory accreditation of organizations in the health system and to integrate quality- and equity-related health service indicators into the national social protection monitoring and evaluation system; these will speed up the progress towards UHC and health security.